Advanced Computing and Systems for Security Volume Three - Chaki, Rituparna; Saeed, Khalid; Cortesi, Agostino; Chaki, Nabendu (Advances in Intelligent Systems and Computing, 2017)
This book presents extended versions of papers originally presented and discussed at the 3rd International Doctoral Symposium on Applied Computation and Security Systems (ACSS 2016) held from August 12 to 14, 2016 in Kolkata, India. The symposium was jointly organized by the AGH University of Science & Technology, Cracow, Poland; Ca' Foscari University, Venice, Italy; and the University of Calcutta, India. The book is divided into two volumes, Volumes 3 and 4, and presents dissertation works in the areas of Image Processing, Biometrics-based Authentication, Soft Computing, Data Mining, Next-Generation Networking and Network Security, Remote Healthcare, Communications, Embedded Systems, Software Engineering and Service Engineering. The first two volumes of the book published the works presented at the ACSS 2015, which was held from May 23 to 25, 2015 in Kolkata, India.